Jakie publiczne prawo gospodarcze? Kontynuacja dyskusji wokół wartości i zasad - Trela, Anna (Studia Prawa Publicznego, 2024)
The discussion on the legitimacy of distinguishing public economic law as a branch of law, undertaken in 1993 in the pages of the journal “Ruch Prawniczy, Ekonomiczny i Socjologiczny,” still arouses much controversy. It may seem that the achievements of the science of public economic law have definitively determined the independence of this branch of law. However, the debate is still ongoing in both Polish, French and German law. This is mainly due to the lack of a single definition of public economic law, the delimitation of its scope and the establishment of a method of regulation. This is not a simple matter, as the subject of public economic law is very complex. It is the economy with all its conditions and the political objectives which are set in this regard that results in public economic law going beyond the traditional division into public and private law. This part of the legal system relating to the economy is constantly developing and changing, as are the ‘new’ legal areas. The spirit of this law is to be sought in the objectives and not in the means used. In doing so, it is emphasised that in order to achieve the objectives, it is necessary to use various methods of action, which are to be increasingly effective from an economic point of view. Therefore, there is a need for multifaceted research requiring a ‘combined research approach’, taking into account various research methods, especially since public economic law is not permanent. The development of its own set of values and principles of law underlines the sectoral distinctiveness of this discipline.